2023
DOI: 10.3390/s23031144
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Useful Life Prediction of Rolling Bearings Using GRU-DeepAR with Adaptive Failure Threshold

Abstract: Aiming at the problem that a single neural network model has difficulty in accurately predicting trends of the remaining useful life of a rolling bearing, a method of predicting the remaining useful life of rolling bearings using a gated recurrent unit-deep autoregressive model (GRU-DeepAR) with an adaptive failure threshold was proposed. First, time domain and frequency domain features were extracted from the rolling bearing vibration signal. Second, its operation process was divided into a smooth operation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…And the DeepAR model is used to predict the slope displacement by Dong [27], which the prediction accuracy of DeepAR model was verified by mean absolute error, root mean square error and goodness of fit. Li et al [28] proposed a method for predicting the residual service life of rolling bearing based on gru-depth autoregressive model with self-adaptive failure threshold [29].…”
Section: Deepar Model Theorymentioning
confidence: 99%
“…And the DeepAR model is used to predict the slope displacement by Dong [27], which the prediction accuracy of DeepAR model was verified by mean absolute error, root mean square error and goodness of fit. Li et al [28] proposed a method for predicting the residual service life of rolling bearing based on gru-depth autoregressive model with self-adaptive failure threshold [29].…”
Section: Deepar Model Theorymentioning
confidence: 99%
“…It is important to note that predicting the RUL directly after the initial degradation stage can save computational costs, improve algorithm efficiency, and enhance model accuracy throughout the entire life evolution of rolling bearings. Therefore, the accurate delineation of the first prediction time (FPT) of rolling bearings has become a key concern [15,16], and more existing methods for determining the FPT are mainly based on the 3σ guidelines [17,18]. Yang et al [19] proposed a continuous gradient identification algorithm to identify the initial degradation time.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al employed a support vector machine (SVM) to distinguish various stages of bearing degradation, which to some extent differentiated normal from faulty stages, but failed to identify the early micro-faults [7]. Li et al extracted traditional health features from the vibration signals of rolling bearings to ascertain the points of deterioration, relying on the trajectory of the cumulative maximum of root mean square (RMS) [8]. Cheng et al developed an adaptive kernel spectral clustering model, which adeptly identified the incipient degradation points of rolling bearings through the adaptive discernment of multidimensional deterioration features amalgamated from the time domain, frequency domain, and time-frequency domain [9].…”
Section: Introductionmentioning
confidence: 99%